Labor Market Effects of Demographic Shifts and Migration in OECD Countries - Docquier, Frederic; Ozden, Caglar; Kone, Zovanga L.; Mattoo, Aaditya; Ozden, Caglar (World Bank, Washington, DC, 2018)
The labor force of each industrial country is being shaped by three forces: ageing, education and migration. Drawing on a new database for the OECD countries and a standard analytical framework, this paper focuses on the relative and aggregate effects of these three forces on wages across different skill and age groups over 2000 to 2010. The variation in the age and educational structure of the labor force emerges as the dominant influence on wage changes. The impact is uniform and egalitarian: in almost all countries, the changes in the age and skill structure favor the low-skilled and hurt the highly skilled across age groups. Immigration plays a relatively minor role, except in a handful of open countries, like Australia and Canada, where it accentuates the wage-equalizing impact of ageing and education. Emigration is the only inegalitarian influence, especially in Ireland and a few Eastern European countries which have seen significant outflows of high-skilled labor to Western European Union countries.